Bill for the planning and development of land Act - Government of the Republic of Trinidad and Tobago (Government of the Republic of Trinidad and Tobago., 2011)
An Act relating to urban and regional planning, development of land and the construction of buildings.
http://www.ttparliament.org/publications.php?mid=28andid=489
Keywords: Development planning Laws - Trinidad and Tobago, Urban planning - Legislation, Land development, Construction - Laws